Acceptability and feasibility of a guided biopsychosocial online intervention for cancer patients undergoing chemotherapy - Grapp, Miriam; Rosenberger, Friederike; Hemlein, Elena; Klein, Eva; Friederich, Hans-Christoph; Maatouk, Imad (Journal of cancer education, 2020)
Chemotherapy is a physically and psychologically highly demanding treatment, and specific Internet-based interventions for cancer patients addressing both physical side effects and emotional distress during chemotherapy are scarce. This study examined the feasibility and acceptability of a guided biopsychosocial online intervention for cancer patients undergoing chemotherapy (OPaCT). A pre-post, within-participant comparison, mixed-methods research design was followed. Patients starting chemotherapy at the outpatient clinic of the National Center for Tumor Diseases in Heidelberg, Germany, were enrolled. Feasibility and acceptability were evaluated through intervention uptake, attrition, adherence and participant satisfaction. As secondary outcomes, PHQ-9, GAD-7, SCNS-SF34-G and CBI-B-D were administered. A total of N = 46 patients participated in the study (female 76.1%). The age of participants ranged from 29 to 70 years (M = 49.3, SD = 11.3). The most prevalent tumour diseases were breast (45.7%), pancreatic (19.6%), ovarian (13.1%) and prostate cancer (10.8%). A total of N = 37 patients (80.4%) completed the OPaCT intervention. Qualitative and quantitative data showed a high degree of participant satisfaction. Significant improvements in the SCNS-SF34 subscale ‘psychological needs’ were found. Study results demonstrate the feasibility and acceptability of the intervention. The results show that OPaCT can be implemented well, both in the treatment process and in participants’ everyday lives. Although it is premature to make any determination regarding the efficacy of the intervention tested in this feasibility study, these results suggest that OPaCT has the potential to reduce unmet psychological care needs of patients undergoing chemotherapy.